Hierarchical ISI-1 zeolite catalyst for hydroconversion of long-chain paraffins. Issue 4 (24th December 2020) - Sree, Sreeprasanth Pulinthanathu; Radhakrishnan, Sambhu; Geerts, Lisa; Van der Donck, Tom; Vanbutsele, Gina; Breynaert, Eric; Seo, Jin Won; Martens, Johan A.
Abstract : The hierarchization via desilication of ISI-1 zeolite, belonging to the TON type family and its impact on catalytic performance in hydroconversion of model long chain  n -alkanes are presented. Abstract : The hierarchization via desilication of a less studied zeolite, but with particular potential for catalytic applications, belonging to the TON type zeolite family, viz. ISI-1, and its impact on catalytic performance in hydroconversion of model long chain n -alkanes are presented. The diffusivity of heavy molecules within monodimensional micropore system zeolites with TON frameworks is limited and the activity is concentrated in the rim of the crystals, referred to as pore mouth catalysis. Desilication has proved to be an efficient strategy for hierarchization, increasing the number of pore mouths as revealed by HR-SEM and TEM. Though notable inhomogeneity in the dispersion of platinum nanoparticles over individual crystals was evidenced via SEM at high resolution, the catalyst presented high isomerization yields.